(untitled) (Global Journal of Science Frontier Research, 2017)
In his paper we obtained a canonical local basis , = 1,5 of vector bundle on Clifford ̈ℎ manifold (, ). The paths of semispray on Clifford ̈ℎ manifold are infact the solutions of Euler-Lagrange equations.